Impact Analysis Of Implementation Of Bonded Warehouse Policy In Makassar Port New Port On Logistic Costs - Yusup, Muhammad Firdaus Bin (Maritime Park: Journal of Maritime Technology and Society, 2022)
The level of industry dependence on imported goods is still very high while logistics costs in Indonesia reach 24 % of total GDP. Therefore, the need for bonded warehouses to improve logistics management inefficiencies. Bonded warehouse according to PMK RI No. 155/PMK.04/2019 is a Bonded Stockpiling Place (TPB) for stockpiling imported goods, may be accompanied by 1 (one) or more activities in the form of packaging/repackaging, sorting,kitting, packing, setting, cutting, for goods certain goods within a certain period of time to be reissued. The advantages of implementing this bonded warehouse are minimizing the distance between business actors and raw materials so as to reduce dwelling time, make the price of raw materials and production more affordable, obtain exemption or deferral facilities from import duties, excise and taxes. However, some areas with great potential do not have bonded warehouses such as Makassar New Port. The analysis of this study is to compare the logistics costs of importing sugar from Thailand with a bonded warehouse in Tanjung Priok with the implementation of a bonded warehouse in Makassar New Port, which can save costs of Rp. 11,062,648,783. So that the placement of a bonded warehouse in Makassar New Port is the right solution.